EVALUATION OF VITAMIN D, CALCIUM, LFTS IN BETA THALASSEMIA PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Beta-thalassemia is a severe hereditary blood disorder characterized by ineffective erythropoiesis, chronic anemia, and iron overload due to frequent blood transfusions. This study evaluates liver function tests (LFTs), serum vitamin D, calcium, and ferritin levels in 200 pediatric patients (110 males, 90 females) with beta-thalassemia major. The biochemical analysis revealed that 55.5% of patients had elevated AST levels (>40 U/L), 22% had ALT >56 U/L, and 10% exhibited ALP >129 U/L, indicating potential liver damage due to iron overload. A striking 99% of patients had vitamin D deficiency (